SIRPB1 promotes prostate cancer cell proliferation via Akt activation. Issue 4 (6th January 2020) - Song, Qiong; Qin, Siyuan; Pascal, Laura E.; Zou, Chunlin; Wang, Wenchu; Tong, Haibo; Zhang, Jian; Catalona, William J.; Dhir, Rajiv; Morrell, Megan; Balasubramani, Goundappa K.; Lu, Yi; et al.
Abstract: Background: Signal regulatory protein β1 (SIRPB1) is a signal regulatory protein member of the immunoglobulin superfamily and is capable of modulating receptor tyrosine kinase‐coupled signaling. Copy number variations at the SIRPB1 locus were previously reported to associate with prostate cancer aggressiveness in patients, however, the role of SIRPB1 in prostate carcinogenesis is unknown. Methods: Fluorescence in situ hybridization and laser‐capture microdissection coupled with quantitative polymerase chain reaction was utilized to determine SIRPB1 gene amplification and messenger RNA expression in prostate cancer specimens. The effect of knockdown of SIRPB1 by RNA interference in PC3 prostate cancer cells on cell growth in colony formation assays and cell mobility in wound‐healing, transwell assays, and cell cycle analysis was determined. Overexpression of SIPRB1 in C4‐2 prostate cancer cells on cell migration, invasion, colony formation and cell cycle progression and tumor take rate in xenografts was also determined. Western blot assay of potential downstream SIRPB1 pathways was also performed. Results: SIRPB1 gene amplification was detected in up to 37.5% of prostate cancer specimens based on in silico analysis of several publicly available datasets. SIRPB1 gene amplification and overexpression were detected in prostate cancer specimens. The knockdown of SIRPB1 significantly suppressed cell growth in colony formation assays and cell mobility. SIRPB1 knockdown also induced cell cycle arrest during the G0 /G1 phase and enhancement of apoptosis. Conversely, overexpression of SIPRB1 in C4‐2 prostate cancer cells significantly enhanced cell migration, invasion, colony formation, and cell cycle progression and increased C4‐2 xenograft tumor take rate in nude mice. Finally, this study presented evidence for SIRPB1 regulation of Akt phosphorylation and showed that Akt inhibition could abolish SIRPB1 stimulation of prostate cancer cell proliferation. Conclusions: These results suggest that SIRPB1 is a potential oncogene capable of activating Akt signaling to stimulate prostate cancer proliferation and could be a biomarker for patients at risk of developing aggressive prostate cancer.